2018
DOI: 10.1186/s12944-018-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Are non-high–density lipoprotein fractions associated with pediatric metabolic syndrome? The CASPIAN-V study

Abstract: BackgroundNon-high-density lipoprotein cholesterol (non-HDL-C) is considered as a valuable predictor for dyslipidemia and subclinical atherosclerosis which can be an appropriate index for identifying individuals with metabolic syndrome (MetS).ObjectiveTo evaluate the association between non-HDL-C MetS and determine the optimal cut-points of non-HDL-C fractions for identifying MetS in Iranian children and adolescents.MethodsThis nationwide study was conducted in the framework of the fifth survey of a national s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…However, all AUC values were in the range of 0.8–0.9 in both genders, suggesting that all atherogenic indices assessed in our study are useful for predicting MetS. Similar results of AUC values for TG/HDL-c index, although slightly lower that in our study, were obtained by Angoorani et al (2018b) in an Iranian population aged 7–18 years. Also, the cutoff points in that study were slightly lower than those reported here.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, all AUC values were in the range of 0.8–0.9 in both genders, suggesting that all atherogenic indices assessed in our study are useful for predicting MetS. Similar results of AUC values for TG/HDL-c index, although slightly lower that in our study, were obtained by Angoorani et al (2018b) in an Iranian population aged 7–18 years. Also, the cutoff points in that study were slightly lower than those reported here.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the cutoff points in that study were slightly lower than those reported here. These differences might be explained by the fact that different MetS diagnostic criteria were employed, IDF in our study and the Adult Treatment Panel III (ATP III) criteria in the study of Angoorani et al (2018b). We have previously suggested that there is a high variability in the existing criteria for the diagnosis of MetS in adolescents (Fernández-Aparicio et al, 2021) and that the IDF’s diagnostic criteria are the most accurate for the prediction of MetS in adolescents using anthropometric indices (Perona et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…After the rejection of duplicates, we screened 415 studies, followed by a full-text assessment for eligibility for 222 papers. Finally, 19 ( 20 38 ) and 5 ( 20 , 25 , 27 , 29 , 31 ) studies were included in the qualitative and quantitative syntheses, respectively. The detailed flow diagram is demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Given the long latency period between tobacco exposure and AS, the identi cation of sensitive bio-markers of dyslipidemia is important for assessment of potential AS 22 . Several studies have recommended the use of non-HDL-C as a valuable predictor for dyslipidemia and cardiovascular risks 23,24 . In the current study, we demonstrated that tobacco actively exposed (current smoking), smoking intensity and burden were all positively associated with higher levels of the AS bio-marker non-HDL-C in the general adult population in Beijing, even after adjusting for several parameters that might affect the result.…”
Section: Discussionmentioning
confidence: 99%